1996
DOI: 10.2307/2082801
|View full text |Cite
|
Sign up to set email alerts
|

Global Political Order, Economic Change, and Armed Conflict: Coevolving Systems and the Use of Force

Abstract: Several recent explanations for major-power war focus on purported cycles in global economic activity or in global political order. I shall argue that a better understanding of interrelationships among the economic long wave, the global leadership cycle, and armed conflict can be gained if we (1) expand the study of interstate conflict beyond the limited domain of great power or systemic wars and (2) treat the long wave and the leadership cycle as quasi-independent and interrelated processes, each contributing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 20 publications
0
67
0
1
Order By: Relevance
“…In this section, we employ MCMCpoissonChange to revisit the empirical test of cyclical theories of great-power war by Pollins (1996). Pollins identifies four core frameworks in the study of cyclical patterns of international conflicts based on "(1) the relative importance of global political versus economic subsystems, (2) the dating of the phases they identify in the cycle, and (3) predictions regarding the level of conflict within particular phases of their respective cycles" (Pollins 1996, 106).…”
Section: A Bayesian Poisson Changepoint Model Examplementioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we employ MCMCpoissonChange to revisit the empirical test of cyclical theories of great-power war by Pollins (1996). Pollins identifies four core frameworks in the study of cyclical patterns of international conflicts based on "(1) the relative importance of global political versus economic subsystems, (2) the dating of the phases they identify in the cycle, and (3) predictions regarding the level of conflict within particular phases of their respective cycles" (Pollins 1996, 106).…”
Section: A Bayesian Poisson Changepoint Model Examplementioning
confidence: 99%
“…These four theories are further diverged in their predictions on the specific cycle phases of international conflicts as shown in Table 4. Following Pollins (1996), we use the annual number of military conflicts from the militarized interstate disputes (MID) data (Jones, Bremer, and Singer 1996) to detect the number and q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q timing of cycle phases in international conflicts.…”
Section: A Bayesian Poisson Changepoint Model Examplementioning
confidence: 99%
“…Perhaps part of the answer rests with competitive imperialisms and the tendency for the world-system to engage in systemic war on a fairly regular basis. Building on the hegemony-rivalry literature, Wallerstein (and a number of others both within and outside of world-systems analysis) suggested that there would be a "war peak" (a period when the chance of global war would be highest) between 2030 and 2050 (Pollins 1996;Denemark 1999). This is not nearly as far off as it was when these works were first published, and certainly the dangers of hegemony-rivalry are becoming more apparent once again and should not be underestimated.…”
Section: On Bringing the State Back Inmentioning
confidence: 99%
“…To explain interstate conflict, some argue for the primacy of economic factors ("the resource view") while others point at the political structure of the international system, with a unicentric arrangement reducing conflict and a multicentric structure inducing it (Arrighi and Silver 1999). 16 Political scientist Brian Pollins (1996) has argued that the general strategies that most researchers utilize in order to deal with this theoretical issue can be classified into three different types: conflation, reduction or co-evolution. Those who conflate economic and political (global order) processes simply do not make any distinction between economic and political systemic properties, or view them as perfectly reducible to one another.…”
Section: Terrorism and Global Long-term Economic Cyclesmentioning
confidence: 99%
“…Chase-Dunn's (1998) world system constants-cycles-trends framework can be a useful organizing device in our consideration of terrorism. It is well known that violent conflict of all types is a constant feature of the interstate system; and research shows that both conflict severity and incidence present cyclical patterns (Goldstein 1988;Pollins 1996). Further, we know that rising conflict severity represents a real trend in the interstate system (Boswell and Sweat 1993;Chase-Dunn 1998).…”
Section: Conclusion: Cross-level Violent Interactions and Hegemonic Dmentioning
confidence: 99%